Pengaruh Social Influence dan Facilitating Conditions Terhadap Behavioral Intention Pengguna e-wallet - Triana, Betha; Suherman, Ujang; Pranata, Rengga Madya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to examine the effect of social influence and facilitating conditions on behavioral intention in using electronic wallets (e-wallets) among students of the Karawang Buana Perjuangan University Management Study Program, both partially and simultaneously. The research sample consisted of 80 respondents selected using purposive sampling technique based on the Slovin formula. Data were collected through a questionnaire instrument with a semantic differential measurement scale. Before further analysis, the research instrument was tested for validity and reliability to ensure the accuracy and consistency of the data. The analysis technique used was multiple linear regression.The results showed that the variables of social Influence and facilitating conditions had a significant effect on behavioral intention in using e-wallets, both individually and simultaneously. This finding indicates that the greater the social Influence and the better the supporting conditions, the higher the intention of students to use e-wallets. The two independent variables together are able to explain 46.1% of the variability in behavioral intention, which indicates that there are other factors outside this model that also influence students' intention to use e-wallets.